2017
DOI: 10.1155/2017/7348372
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Protein 2: A Key Player and a Potential Therapeutic Target in Vascular Diseases

Abstract: Uncoupling protein 2 (UCP2) is an inner mitochondrial membrane protein that belongs to the uncoupling protein family and plays an important role in lowering mitochondrial membrane potential and dissipating metabolic energy with prevention of oxidative stress accumulation. In the present article, we will review the evidence that UCP2, as a consequence of its roles within the mitochondria, represents a critical player in the predisposition to vascular disease development in both animal models and in humans, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 117 publications
1
57
0
Order By: Relevance
“…UCP2 gene variants were found to be associated with reduced insulin sensitivity and obesity [ 13 ], metabolic syndrome [ 14 ], prediabetes and type 2 diabetes mellitus [ 15 , 16 ], hypertension [ 17 ], coronary artery disease [ 18 ], and stroke outcome [ 19 ]. This supports data obtained in cellular and experimental animal models and suggests that UCP2 is a potential therapeutic target for major metabolic and cardiovascular diseases [ 1 ].…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…UCP2 gene variants were found to be associated with reduced insulin sensitivity and obesity [ 13 ], metabolic syndrome [ 14 ], prediabetes and type 2 diabetes mellitus [ 15 , 16 ], hypertension [ 17 ], coronary artery disease [ 18 ], and stroke outcome [ 19 ]. This supports data obtained in cellular and experimental animal models and suggests that UCP2 is a potential therapeutic target for major metabolic and cardiovascular diseases [ 1 ].…”
Section: Introductionsupporting
confidence: 89%
“…Uncoupling protein-2 (UCP2) is a mitochondrial anion carrier protein, which uncouples oxidative phosphorylation from ATP production by dissipating the proton gradient generated across the inner mitochondrial membrane [ 1 , 2 , 3 ]. UCP2 is protective against oxidative damage by reducing the amount of reactive oxygen species (ROS), produced during oxidative phosphorylation by the electron transport chain [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that decreases in weight gain and adiposity in younger mice fed a HFD-WPI might be linked with eWAT catabolism. Cpt1a and Ucp2 are genes coding, respectively, for a mitochondrial enzyme that catalyses the rate-limiting step of fatty acids β-oxidation and a mitochondrial membrane protein that dissipates metabolic energy with prevention of oxidative stress accumulation (Bäckhed, Manchester, Semenkovich, & Gordon, 2007;Horvath et al, 2003;Pierelli et al, 2017;Warfel et al, 2017). While these two genes were expressed more in mice fed a HFD-WPI when younger, Hsl and Lpl genes, together with the gene coding for LPL-fasting induced inhibitor FIAF (also involved in triglyceride metabolism), were expressed less in the same group, compared to 5w mice fed with HFD-CAS.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible mechanism to partially explain the observed associations is that polymorphisms or haplotypes of UCPs could alter UCP functions and predispose to cardiovascular risk or an increased Risk Score (due to it is make up of cardiovascular risk factors). This dysfunction may explain the phenotypes observed with CVD risk through, i) dysfunction of the process of oxidation of fatty acids, leading to altered serum lipid levels as TC, LDL, HDL or TG (9,15), ii) in relation to ROS regulation mediated by UCP2; Pierelli et al (37) showed that knockout mice deletion of the UCP2 gene contributes to atherosclerosis lesion development and a significantly shorter lifespan. Several studies in humans and cultured cells suggested that excessive ROS production is involved in the atherosclerotic plaque formation and progression (38,39).…”
Section: Discussionmentioning
confidence: 99%